1993
DOI: 10.1038/sj.bdj.4808263
|View full text |Cite
|
Sign up to set email alerts
|

A randomised trial of co-amoxiclav (Augmentin) versus penicillin V in the treatment of acute dentoalveolar abscess

Abstract: In a randomised, operator-blind, comparative clinical trial, the efficacy of co-amoxiclav (250 mg amoxycillin plus 125 mg clavulanic acid, eight-hourly) was compared to that of penicillin V (250 mg phenoxymethylpenicillin, six-hourly) in the treatment of acute dentoalveolar abscess. In each case surgical drainage was established at the time of initial presentation by incision of any soft tissue swelling, accompanied by either extraction of the tooth or extirpation of the pulp as indicated clinically. Each pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 0 publications
1
33
0
4
Order By: Relevance
“…This may be related to the eradication of the betalactamase producers with co-amoxiclav that would not be eradicated by penicillin V. 54 All of these data support the contention that phenoxymethylpenicillin should not be the fi rst choice of antibiotic for dentoalveolar infections.…”
Section: Resistance Changesmentioning
confidence: 80%
See 2 more Smart Citations
“…This may be related to the eradication of the betalactamase producers with co-amoxiclav that would not be eradicated by penicillin V. 54 All of these data support the contention that phenoxymethylpenicillin should not be the fi rst choice of antibiotic for dentoalveolar infections.…”
Section: Resistance Changesmentioning
confidence: 80%
“…34,48,52 Penicillin resistant bacteria are often present in the micro-fl ora of acute dental infections. [53][54][55] Eick et al 57 showed that the majority of micro-organisms isolated from pus from dento-alveolar abscesses were Gram negative anaerobes and were highly susceptible to metronidazole and clindamycin, but that 22% of isolated bacteria produced beta-lactamases and were resistant to penicillin.…”
Section: Resistance Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…This optimises the therapeutic benefits of the antibiotic to the patient while minimising the risks of increasing microbial resistance. There is increasing evidence that many of the responsible oral flora are becoming resistant to penicillin [59][60][61][62] and a number of studies have advocated the benefits of clindamycin as the first choice antibiotic for dentoalveolar abscess management in patients with evidence of systemic involvement. 24,35,47,62,65,69,71,80 …”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54] Radical changes in prescribing habits and recognition of the increasing levels of resistant micro-organisms are needed to slow this ever-increasing trend. 8,51,[53][54][55][56][57][58][59][60][61][62] It is now clear that indiscriminate usage of antibiotics has contributed to this massive increase of resistant bacteria. As a consequence the European Centre for Disease Prevention launched the first European Antibiotics Awareness Day on 18 November 2008.…”
Section: Discussionmentioning
confidence: 99%